Expressed Emotion and behaviourally controlling interactions in the daily life of dyads experiencing psychosis. (30th November 2016) - Vasconcelos e Sa, Debora; Wearden, Alison; Hartley, Samantha; Emsley, Richard; Barrowclough, Christine
Abstract: While research using Experience Sampling Methodology (ESM) suggests that, in general, contact with relatives or friends may be protective for psychotic experiences, contact with high-Expressed Emotion (high-EE) relatives can have adverse consequences for patients. This study investigated whether contact with high-EE relatives, and relatives' behaviourally controlling interactions (BCI) are related to patients' symptoms and to both patients' and relatives' affect when measured using structured diary assessments in the course of everyday life. Twenty-one patients experiencing psychosis and their closest relatives provided synchronized self-reports of symptoms (patients only), affect, dyadic contact and BCI over a 6-days period. Relatives' EE was obtained from Camberwell Family Interviews. Multi-level modeling showed that patients' reports of relatives taking control of them and helping them were associated with increased patient negative affect and symptoms. Relatives' self-reports of nagging, taking control and keeping an eye on the patient were related to fluctuations in relatives' affect. No evidence was found for the moderating effect of EE status on the association between dyadic contact and affect or, in the case of patients, symptoms. When measured using an ecologically valid methodology, momentary behaviourally controlling interactions within dyads experiencing psychosis can impact on patients' affect and symptoms. Highlights: Patients' reports of relatives taking control of them were associated with higher symptoms levels. Patients' reports of their relatives helping them predicted increases in negative mood. Relatives'reports of certain BCI were linked with fluctuations in relatives' mood. Relatives' reports of BCI were not linked with patients' symptoms. Daily life contact with high-EE relatives had no association with patients' affect or symptoms.